DNA methyltransferase 1 and Krüppel-like factor 4 axis regulates macrophage inflammation and atherosclerosis. (March 2019) - Tang, Run-Ze; Zhu, Juan-Juan; Yang, Fang-Fang; Zhang, Yun-Peng; Xie, Si-An; Liu, Yue-Feng; Yao, Wei-Juan; Pang, Wei; Han, Li-Li; Kong, Wei; Wang, Ying-Xiao; Zhang, Tao; et al.
Abstract: Macrophage-mediated inflammatory responses occur throughout all stages of atherosclerosis. DNA methylation is one of the critical epigenetic mechanisms and is associated with the development of atherosclerosis. The underlying mechanism of epigenetic regulation of macrophage inflammation (M1 activation) remains unclear. Here we aim to study the role of DNA methyltransferase 1 (DNMT1) in modulating macrophage inflammation and atherosclerosis. DNMT1 expression is up-regulated in THP-1-derived macrophages upon treatment with lipopolysaccharide (LPS) and interferon-gamma (IFN-γ). Overexpression of DNMT1 promotes the LPS- and IFN-γ-induced M1 activation whereas inhibition of DNMT1 attenuates it. Consistently, DNMT1 expression is elevated in macrophages in atherosclerotic plaques from human and mouse specimens; compared with the Dnmt1wild-type, myeloid Dnmt1 deficiency in mice in an Apolipoprotein E (ApoE) knockout background or receiving AAV-PSCK9 injection and carotid partial ligation results in ameliorated atheroma formation and suppressed plaque inflammation. The promoter regions of atheroprotective Krüppel-like factor 4 (KLF4) are hypermethylated in M1- activated macrophages. DNMT1 down-regulates the expression of KLF4, probably through catalyzing DNA methylation of the promoter regions of KLF4. Gain- and loss-of function study of KLF4 indicates that the DNMT1-mediated macrophage M1 activation is dependent on KLF4. Our data demonstrate a proatherogenic role for DNMT1 as a defining factor in macrophage inflammation both in vitro and in vivo . DNMT1 promotes macrophage M1 activation by suppressing KLF4 expression. Thus macrophage-specific DNMT1 inhibition may provide an attractive therapeutic potential to prevent or reduce atherosclerosis.